Mengeksplorasi Dampak Media Sosial Dalam Komunikasi Krisis: Tinjauan Sistematis Terhadap Social-Mediated Crisis Communication (Smcc) - Pramata, Delvin (Syntax Literate, 2025)
The evolution of social media has compelled numerous organizations to modify their strategies and systems to effectively address crisis situations. The Social-Mediated Crisis Communication (SMCC) model represents a significant innovation in the field of crisis communication management. This model emphasizes the importance of understanding how the public utilizes social media to seek information during crises and how organizations can engage effectively to mitigate negative impacts. With systematic literature review method, this study collected journal articles from the past five years, resulting in the identification of 15 relevant publications. The findings revealed that social media has become a pivotal tool for crisis communication across various industries. It showed by a shared global perception of the critical role social media plays in information dissemination, the continual evolution of communication models mediated by SMCC, and the use of social media by organizations and the public during critical periods such as the COVID-19 pandemic and disaster management efforts. Furthermore, the research highlights the significant role of social media influencers in shaping public opinion. The SMCC model proves to be effective for various entities, including governments and private organizations, in restoring their image and reputation during crises. Amidst rapid technological advancements, the application of SMCC is becoming increasingly relevant and essential in navigating the dynamic landscape of communication.